Antimicrobial oxygen-loaded nanobubbles as promising tools to promote wound healing in hypoxic human keratinocytes. (2022) - Banche, Giuliana; Allizond, Valeria; Mandras, Narcisa; Finesso, Nicole; Luganini, Anna; Genova, Tullio; Argenziano, Monica; Magnetto, Chiara; Gulino, Giulia Rossana; Roana, Janira; Tullio, Vivian; Giribaldi, Giuliana; et al.
Graphical abstract: Highlights: Chitosan-shelled/perfluoropentane-filled OLNBs are innovative oxygen nanocarriers. OLNBs are biocompatible with human keratinocytes after cell internalization. OLNBs promote normoxia-like migration of hypoxic human keratinocytes. Chitosan-shelled OLNBs display antimicrobial activity against MRSA and C. albicans. Oxygen-loaded nanobubbles appear promising tools to treat infected chronic wounds. Abstract: Chronic wounds (CWs) are typically characterized by persistent hypoxia, exacerbated inflammation, and impaired skin tissue remodeling. Additionally, CWs are often worsened by microbial infections. Oxygen-loaded nanobubbles (OLNBs), displaying a peculiar structure based on oxygen-solving perfluorocarbons such as perfluoropentane in the inner core and polysaccharydes including chitosan in the outer shell, have proven effective in delivering oxygen to hypoxic tissues. Antimicrobial properties have been largely reported for chitosan. In the present work chitosan/perfluoropentane OLNBs were challenged for biocompatibility with human skin cells and ability to promote wound healing processes, as well as for their antimicrobial properties against methicillin-resistant Staphylococcus aureus (MRSA) and Candida albicans . After cellular internalization, OLNBs were not toxic to human keratinocytes (HaCaT), whereas oxygen-free NBs (OFNBs) slightly affected their viability. Hypoxia-dependent inhibition of keratinocyte migratory ability after scratch was fully reversed by OLNBs, but not OFNBs. Both OLNBs and OFNBs exerted chitosan-induced short-term bacteriostatic activity against MRSA (up to 6 h) and long-term fungistatic activity against C. albicans (up to 24 h). Short-term antibacterial activity associated with NB prolonged adhesion to MRSA cell wall (up to 24 h) while long-term antifungal activity followed NB early internalization by C. albicans (already after 3 h of incubation). Taken altogether, these data support chitosan-shelled and perfluoropentane-cored OLNB potential as innovative, promising, non-toxic, and cost-effective antimicrobial devices promoting repair processes to be used for treatment of MRSA- and C. albicans -infected CWs.